Peran Media Penyiaran di Era Revolusi Industri 4.0 - Kholilul Kholik (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2021)
The rapid development of information and communication technology in the era of the industrial revolution 4.0 has brought many changes and implications for the world of broadcasting, namely the presence of new broadcast media. However, the presence of these broadcasting media has not been accommodated in broadcasting regulations, namely Law Number 32 of 2002 concerning Broadcasting so that the principles of broadcasting that apply in Indonesia have not been implemented properly. Broadcast media is very much needed in people's lives, which is considered a tool to disseminate information needed by the public. The method used in this research is a qualitative approach with discourse analysis. The results obtained in this research are related to that the media has a strategic role in providing information to the public which includes religious, political, economic and social aspects so that the community or the public can know the conditions of the region and the State and can reveal cultural identity nationally without distinguishing groups or groups. ethnic group.